Routing in mobile ad hoc networks using fuzzy neural networks - Sova, Oleg; Romanjuk, Valeriy; Minochkin, Dmytro (Видавництво Львівської політехніки, 2010)
In this article the use of fuzzy neural networks is offered for the construction of management routing subsystem in Mobile Ad Hoc Networks.
Keywords: Mobile Ad Hoc Networks (MANET); dynamic topology; Routing; fuzzy neural networks